Formadores en la indústria avícola: actores clave en situación difícil - Céline Chatigny; André Balleux (Universidade do Porto, 2006)
This exploratory study examines the dynamics among three types of players involved in task training at three plants in the Québec poultry industry: training managers, instructors and apprentices (Chatigny et al., 2005). The main objective is to identify obstacles to implementation of training intended to facilitate the integrated learning of task-related skills and those related to occupational health and safety. The data is obtained from video recordings of interviews carried out during a study conducted by Richard et al. (2002) at three enterprises. Complementary interviews were conducted to contextualize and supplement the data analysis. The results show that trainers comprise three groups of stakeholders that include subgroups whose situations and needs vary. Moreover, trainers fulfil various roles as they create and maintain favourable dynamics for training and learning. Trainers are key intermediaries in the manager/apprentice relationship and in aspects related to task learning, OHS and training and production management. Participating companies recognized the importance of the evolution of training, but tend to favour a Taylorian logic to instructors´ and apprentices´ work and learning situations.